Melepas Masa Lalu Perjuangan Menuju Kehidupan Baru Studi Kasus Mantan PSP di Kawasan Pantura Batang (International Forum of Researchers and Lecturers, 2024)
This research aims to explore the dynamics of the lives of women who have worked as female sex workers in their efforts to live a life that is considered normal by society after being involved in the prostitution business. This research also seeks to identify the motivating factors that encourage these women to leave the profession and switch to a life that is in line with the values ​​and norms prevailing in society. The research methods used include in-depth interviews and participant observation to understand the challenges, adaptation process, and social support that play a role in their reintegration process. It is hoped that the research results will provide insight into their transformation journey, the social and psychological obstacles they face, as well as the crucial factors that play a role in helping them rediscover their identity and social roles that are recognized in their community. It is hoped that these findings can provide input for policy makers and social institutions in designing effective rehabilitation and reintegration programs.